Analytical and Policy Aspects of Financial Programming : The Case of Egypt - Rached, Mounir (International Monetary Fund, 1990)
The formulation and use of a financial program are the main focus of this book which is used in the Arabic course on financial analysis and policy offered by the IMF Institute. This volume, written by Taher Dajani, Samir El-Khouri, Mohamed Hosny, and Mounir Rached, will be of interest to policymakers and to others in financial planning.